Systemic risk, bank’s capital buffer, and leverage - Buddi Wibowo (Universitas Islam Indonesia, 2017)
This paper measures individual bank’s impact on banking systemic risk and examines the effect of individual bank’s capital buffer and leverage to bank’s systemic risk impact in Indonesia during 2010-2014. Using Merton’s distance-to-default to measure systemic risk, the study shows a significant negative relationship between bank’s capital buffer and systemic risk. High capital buffer tends to lowering bank’s impact on systemic risk. Bank’s leverage level also influences its contribution to systemic risk, even though the impact is much lower compared to that of capital buffer impact.